ШЛЯХИ ВПРОВАДЖЕННЯ ДОСВІДУ АВТОРСЬКИХ ШКІЛ У ПРОФЕСІЙНУ ПІДГОТОВКУ ВЧИТЕЛЯ МУЗИКИ (Педагогіка вищої та середньої школи, 2022)
In article the structure of semantic model of vocational I mining o f the teacher o f music is considered. The system of interactions o f components o f structure on a polyphonic basis is analyzed. Such spheres of polyphonic structure, as formationintegration knowledge, poly-art skills, complex feelings, personal senses come to light.